Supramolecular Strategies for Controlling Reactivity within Confined Nanospaces - Wang, Kaiya; Jordan, Jacobs H.; Hu, Xiao‐Yu; Wang, Leyong (Angewandte Chemie International Edition, 2020)
Nanospaces are ubiquitous in the realm of biological systems and are of significant interest among supramolecular chemists. Understanding chemical behavior within nanospaces offers new perspectives on biological phenomena in nature and opens the way to highly unusual and selective forms of catalysis. Supramolecular chemistry exploits weak, yet effective, intermolecular interactions such as hydrogen bonding, metal‐ligand coordination, and the hydrophobic effect to assemble nano‐sized molecular architectures, providing reactions with remarkable rate acceleration, substrate specificity, and product selectivity. In this minireview, the focus is on the strategies that supramolecular chemists use to emulate the efficiency of biological processes, and elucidating how chemical reactivity is efficiently controlled within well‐defined nanospaces. Approaches such as orientation and proximity of substrate, transition‐state stabilization, and active‐site incorporation will be discussed. Three supramolecular strategies to control reactivity within nanospaces are presented. These nano‐environments may: 1) restrict substrate conformation and enforce preorganization; 2) allow for stabilization of transition state; or 3) incorporate with the requisite active site or an additional catalyst. The synergistic effects may result in rather large rate accelerations and high selectivity.